U-PB AND LU-HF IN ZIRCON DECIPHERING MAGMATIC PULSES OF THE JUÍNA KIMBERLITE: IMPLICATIONS FOR THE LITHOSPHERIC MANTLE ISOTOPIC COMPOSITION OF THE AMAZONIAN CRATON - Coelho, Marco Helenio de Paula Alves; Martins, Maria Virginia Alves; Tavares Jr., Armando Dias; Muniz, Leticia; Romero, Luiz Felipe; Paiva, Gabriel Alves; Zan, Willian Giovani; Weska, Ricardo Kalikowski Weska; Geraldes, Mauro Cesar (Boletim Paranaense de Geociências, 2022)
This work aims to analyze U-Pb and Lu-Hf ages in zircons formed together with diamonds from the kimberlite province of Juína, in Mato Grosso state, Brazil. Fourteen megacryst (2-3 cm) of zircon were imaged by cathodoluminescence to evaluate the internal structure of the zircon grains and zoning features related to structures of reactions and resorption indicative of magma mixture during evolution. According to the taken images, most of the investigated crystals have a non-metamict structure, with rare fractures, inclusions, and overgrowths, which generates a small degree of heterogeneity. Analyses by Laser Ablation- Multi-Collector- Inductively Coupled Plasma Mass Spectrometry (LA-MC-ICP-MS) were performed to determine grain ages. Concordia diagrams indicate ages ranging from 99.8 ± 1.6 Ma to 89.5 ± 5.6 Ma with two clusters indicating different magmatic pulses. The analyzed zircons displayed total concentrations of U and Th ranging from 108 to 673 mg kg-1 and 26 to 194 mg kg-1, respectively, and U/Th values varying between 4 and 0.3. The concentrations of U and Pb suggest the occurrence of magmas with two distinct signature components. One hundred and twenty Lu-Hf isotopic results obtained by LA-MC-ICP-MS indicate homogeneity in the isotopic composition, with εHf values ranging from +2.2 to -1.9, and depleted mantle model ages (TDM) between 1.45 Ga and 2.55 Ga. The results suggest that the kimberlite magma derives from a mantle source enriched with an Hf isotopic signature equivalent to the chondritic unfractionated reservoir (CHUR).